GmNAC5, a NAC Transcription Factor, Is a Transient Response Regulator Induced by Abiotic Stress in Soybean. (28th July 2013) - Jin, Hangxia; Xu, Guangli; Meng, Qingchang; Huang, Fang; Yu, Deyue
Abstract : GmNAC5 is a member of NAM subfamily belonging to NAC transcription factors in soybean ( Glycine max (L.) Merr.). Studies on NAC transcription factors have shown that this family functioned in the regulation of shoot apical meristem (SAM), hormone signalling, and stress responses. In this study, we examined the expression levels of GmNAC5 . GmNAC5 was highly expressed in the roots and immature seeds, especially strongly in immature seeds of 40 days after flowering. In addition, we found that GmNAC5 was induced by mechanical wounding, high salinity, and cold treatments but was not induced by abscisic acid (ABA). The subcellular localization assay suggested that GmNAC5 was targeted at nucleus. Together, it was suggested that GmNAC5 might be involved in seed development and abiotic stress responses in soybean.